ASSESSING PATIENT SATISFACTION IN GYNAECOLOGY AND OBSTETRICS IN TERTIARY CARE HOSPITAL - Hussain, Shahzadi Saima; Pervez, Khawaja Fawad; Izzat, Saadia (Journal of Postgraduate Medical Institute, 2015)
Objective: To assess patient satisfaction in gynaecology and obstetrics in Tertiary care hospital and to highlight the areas of improvement. Methodology: This cross sectional study was conducted in Gynaecology andObstetrics unit B in Lady reading hospital Peshawar. Admitted Patients (whostayed in hospital for at least two days) were given an option to consent toinclusion in the study after consenting. Provided with a set of pre-furnishedquestions regarding the level of communication, satisfaction of treatment aswell as the hygiene of the hospital was observed. Data was analyzed on SPSS10.0 for descriptive data. Results: A total of 1847 patients participated in this study. 90.9% (n=1679) of patients were satisfied with their treatment, 89%( n=1645) patients had confidence in their doctor's competency, 60%(n= 1109) thought treatment was easily affordable, cleanliness could satisfy 20% (n= 387) of patients, andthe way doctors greeted their patients could satisfy 17%(n= 312) of patients,5%( n=109) of patients were called by their names. 11% (n=218) of patients reported that their disease and reason of tests were explained to them. Communications kills of doctors and hospital cleanliness are the areas which requireimprovement. Conclusion: Our Study Suggests that there is an imperative need to communicateeffectively with the patients about their disease and the treatment, itwill help to remove anxiety and misconceptions, and they will comply withthe treatment and develop confidence in the health system for achieving thestandards of good health.